"Ἐπιμερισμοὶ κατὰ στοιχεῖον γραφικὰ" καὶ Ἰαμβικοὶ Κανόνες Χριστουγέννων, Φώτων καὶ Πεντηκοστῆς - ΓΚΕΝΑΚΟΥ-ΜΠΟΡΟΒΙΛΟΥ, Αφροδίτη (Byzantina Symmeikta, 2010)
ΕΠΙΜΕΡΙΣΜΟΙ ΚΑΤΑ ΣΤΟΙΧΕΙΟΝ ΓΡΑΦΙΚΑ AND IAMBIC CANONS FOR CHRISTMAS, EPIPHANY AND PENTECOST This article focuses on the sources of the text Ἐπιμερισμοὶ κατὰ στοιχεῑον γραφικά, and on their relation with the iambic canons for Christmas, Epiphany and Pentecost attributed to St John Damascene. The so called Ἐπιμερισμοὶ is further compared to the small Lexicon referring to the same canons and attributed to the monk Theodosius. Taking as a point of departure the text attributed to John Damascene and analyzing the use of words herewith we arrive to the conclusion that the anonymous compiler of the Επιμερισμοί has borrowed from Theodosius’ Lexicon most of the words and relevant explanations he uses, as well as individual explanations which are used cut off from the original word which they explain. In the Ἐπιμερισμοί, certain difficult words employed in the iambic canons are interpreted; moreover, in the same text, entire phrases are used as an example of the use of the Greek language. The reason why the relation between these texts is analyzed here is to reveal the way in which the Ἐπιμερισμοὶ were composed and the particular ways the author employed to compile his text.